Complete histopathological regression in rectal cancer after neoadjuvant chemoradiotherapy and sphincter preserving surgical treatment - Petrović Tomislav; Knežević-Ušaj Slavica; Radovanović Dragana; Lukić Dejan; Petrović Nemanja; Petroivić Tanja (Vojnosanitetski Pregled)
Background/Aim. Multimodal approach to locally advanced rectal cancer treatment results in better disease outcome. Preoperative chemoradiotherapy improves disease local control, reduces risk of local recurrence and in the majority of patients with complete or substantial regression of the tumors significantly improves survival rates. According to the literature data, approximately 20% of patients had achieved complete histopathological response (pCR) after neoadjuvant chemoradiation therapy. The aim of this study was to evaluate overall survival in rectal cancer patients treated with preoperative chemoradiotherapy and sphincter preserving surgery. Methods. This retrospective study included 191 patients. Patients received preoperative radiation therapy and chemotherapy-chemoradiation therapy (CRT) followed by operation that favorized sphincter preservation with total mesorectal excision (TME) from June 2000 until December 2010. Diagnosis was established according to the following algorithm: patient history, digital rectal examiantion, colonoscopy with biopsy and histopathology verification, and preoperative clinical staging. Patients with tumors located below promontorium were included in the study and patients with metastatic disease and local recurrence were excluded from the study. For tumors located below the promontorium preoperative radiotherapy was used with total dose of 50.4 Gy, divided into daily doses of 1.8 Gy, during 28 days. Chemotherapy followed radiotherapy with 5- fluorouracil and folic acid (Leucovorin®) on days 1, 2, 10, 11, 20 and 21. Six to ten weeks after neoadjuvant therapy, magnetic resonance imaging (MRI) to restage tumors and operation were performed. Results. Of all patients that received preopertive chemoradiation, 163 had radical sphincter preservig surgery and 28 patients had paliative operations. Histopathological examination of the specimens showed that the complete histopathological regression was achieved in 21.4% of the patients, downstaged was found in 63.2% of them and unchanged stage was found in 15.3% of the patients. The five-year survival rate was 63.3% and 50.5 % in the patients with pCR and patients with incomplete histopathological regression, respectively. Survival rates between two groups were not statistically significant (p > 0.05). Conclusion. The preoperative chemoradiotherapy is very important in achieving optimal clinical care for patients with locally advanced rectal cancer.